Molecular characterization of carbendazim resistance of Fusarium species complex that causes sugarcane pokkah boeng disease - Shiqiang Xu; Jihua Wang; Haixuan Wang; Yixue Bao; Yisha Li; Muralidharan Govindaraju; Wei Yao; Baoshan Chen; Muqing Zhang (BMC Genomics, 2019)
Abstract Background Pokkah boeng is one of the most serious and devastating diseases of sugarcane and causes significant loss in cane yield and sugar content. Although carbendazim is widely used to prevent fungal diseases, the molecular basis of Fusarium species complex (FSC) resistance to carbendazim remains unknown. Results The EC50 (fungicide concentration that inhibits 50% of mycelial growth) values of carbendazim for 35 FSC isolates collected in cane growing regions of China were ranged from 0.5097 to 0.6941 μg mL− 1 of active ingredient (a.i.), in an average of 0.5957 μg a.i. mL− 1. Among carbendazim-induced mutant strains, SJ51M (F. verticillioides) had a CTG rather than CAG codon (Q134L) at position 134 of the FVER_09254 gene, whereas in the mutant strain HC30M (F. proliferatum) codon ACA at position 351 of the FPRO_07779 gene was replaced by ATA (T351I). Gene expression profiling analysis was performed for SJ51M and its corresponding wild type strain SJ51, with and without carbendazim treatment. The gene expression patterns in SJ51 and SJ51M changed greatly as evidenced by the detection of 850 differentially expressed genes (DEGs). Functional categorization indicated that genes associated with oxidation-reduction process, ATP binding, integral component of membrane, transmembrane transport and response to stress showed the largest expression changes between SJ51M and SJ51. The expression levels of many genes involved in fungicide resistance, such as detoxification enzymes, drug efflux transporters and response to stress, were up-regulated in SJ51M compared to SJ51 with and without carbendazim treatment. Conclusion FSC was sensitive to carbendazim and had the potential for rapid development of carbendazim resistance. The transcriptome data provided insight into the molecular pathways involved in FSC carbendazim resistance.